2014
DOI: 10.1080/00221341.2014.894110
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Based Learning to Foster Deep Learning in Preservice Geography Teacher Education

Abstract: In South Africa, geography education students' approach to deep learning has received little attention. Therefore the purpose of this one-shot experimental case study was to evaluate the extent to which first-year geography education students used deep or surface learning in an embedded problem-based learning (PBL) format. The researchers measured students' approach to learning in this PBL format in two groups of first-year students (2012 and 2013), using the standardized revised study process questionnaire ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 62 publications
0
17
0
4
Order By: Relevance
“…Since PBL has been shown to be a useful approach in higher education and, more specifically, teacher preparation (e.g., Choi & Yang, 2011;Edwards & Hammer, 2006;Golightly & Raath, 2015;Hushman & Napper-Owen, 2011;Yoon, Woo, Treagust, & Chandrasegaran, 2014;Zhang, Lundeberg, Koehler, & Eberhardt, 2011), we developed the described PBL environment using video cases in a secondary teacher preparation course on the topic of classroom disruptions. PBL also has elements of direct instruction, so although we were convinced of its usefulness in preparing teachers for the classroom, we assumed that it should not be implemented without specific adaptations in this phase of teacher training.…”
Section: Objectivesmentioning
confidence: 99%
“…Since PBL has been shown to be a useful approach in higher education and, more specifically, teacher preparation (e.g., Choi & Yang, 2011;Edwards & Hammer, 2006;Golightly & Raath, 2015;Hushman & Napper-Owen, 2011;Yoon, Woo, Treagust, & Chandrasegaran, 2014;Zhang, Lundeberg, Koehler, & Eberhardt, 2011), we developed the described PBL environment using video cases in a secondary teacher preparation course on the topic of classroom disruptions. PBL also has elements of direct instruction, so although we were convinced of its usefulness in preparing teachers for the classroom, we assumed that it should not be implemented without specific adaptations in this phase of teacher training.…”
Section: Objectivesmentioning
confidence: 99%
“…This interest is based on previous work by Säljö (1976a, 1976b), who used qualitative analysis to examine differences in students' approaches to written texts. The literature differentiates between a deep and a surface strategy to learning (Biggs, 1987;Golightly and Raath, 2015;Yongjun and Reese, 2014;Vanthournout et al, 2014). A deep learning strategy is characterized by the learner's search for the meaning of the information, and by intrinsic motivation.…”
Section: Learning Strategiesmentioning
confidence: 99%
“…This cognitive process of AL is associated with deep learning that arguably takes place in the cognitive engagement stage (Ito, 2017), as opposed to surface learning (Revell & Wainwight, 2009;Tangney, 2014). Whereas surface learning is acquired through extrinsically motivated processes, entailing the accumulation of information, deep learning occurs through an intrinsically motivated process of meaning construction (Golightly & Raath, 2015). Diamond et al (2008, p. 118) observed that "[a] key outcome of deep learning is the ability to apply concepts acquired in one context to a variety of new situations."…”
Section: Definitionsmentioning
confidence: 99%